Utilization of Electrochemical Sensors and Biosensors in Biochemistry and Molecular Biology - Adam, Vojtech; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
Editorial note concerning the "Utilization of Electrochemical Sensors and Biosensors in Biochemistry and Molecular Biology" special issue.
Keywords: Utilization of Electrochemical Sensors and Biosensors in Biochemistry and Molecular Biology